Impacts of Arabic Language and Literature on Khawaja Farid’s Saraiki Poetic Work - Abdul Majeed, Hafiz; Ullah, Irshad (Journal of Islamic and Religious Studies, 2022)
Khawaja Ghulam Farid, the Rūmī of Sira’īkī language, is one of the famous Sufi poets of South Asia who is popular among the public and elite alike due to his scholarly position, intellectual stature, and poetic excellence. The influence of the Arabic language is clear in his poetry, but this influence seems to be more reflected from the Qur'ān, Ḥadīth and Sufism than from Arabic prose or Arabic poetry. Intellectually, it is difficult to understand depth of the meanings and demands of his words without the use of Arabic words. The use of hints from Qur’ānic and Islamic history in a simple, easy, and clear manner increases the effectiveness of his poetry. Short and eloquent Arabic sentences have been made a permanent part of Kāfī’s with great skill, their accuracy and intellectual depth have become evidences, as well as the beauty of speech and emphasis have also led to an increase in expression. The main theme of his poetry is the idea waḥdah al-wajūd. It would be absurd to call him the best and most effective exponent of the theory of waḥdah al-wajūd in his era.